Planning and operation of a hydrogen supply chain network based on the off-grid wind-hydrogen coupling system. (21st August 2020) - Yang, Guoming; Jiang, Yuewen; You, Shi
Abstract: Although hydrogen is identified to be the first choice of the energy industry in the future society, the severe shortage of hydrogen infrastructure hinders the development of the hydrogen economy. Therefore, by simultaneously integrating the planning and operation issues of a hydrogen supply chain network (HSCN) and taking the hydrogen demand of hydrogen fuel vehicles into account, this paper proposes a general optimization design model for a HSCN based on the off-grid wind-hydrogen coupling system to realize the scientific layout of hydrogen infrastructure and stimulate the transition of hydrogen energy. The uncertainties on both sides of the source and load of a HSCN are well-considered. Therein, the uncertainty of wind power is handled with chance constrained programming, while the uncertainty of hydrogen demand is addressed by a density-based clustering approach. The analysis focuses on a HSCN of Fujian Province, China and case study is conducted. Results show that the estimated hydrogen demand in Fujian Province over the course of a year is 0.197 million tons. The hydrogen production is located in Fuzhou, Quanzhou and Xiamen and the daily hydrogen production in Fuzhou is 309.11 ton/day, accounting for 57.48% of the total hydrogen production in Fujian Province. Since the revenue of the energy storage batteries cannot offset its high investment cost, the abnegation of the energy storage batteries in the HSCN is obtained. Compared with the deterministic HSCN, the total cost of the HSCN considering the uncertainties of wind power and hydrogen demand is reduced by 1.35%. The Levelized cost of hydrogen is 3.073–3.155/kg and hydrogen production shows a significant scale effect. These results could provide information and direction to stakeholders, investors and policymakers for the planning of the future HSCN in Fujian Province to promote the tremendous development of the hydrogen industry. Highlights: A mathematical model for designing and scheduling of a HSCN is proposed. The wind power curtailment in the analysis of a HSCN system is introduced. A DBSCAN-based technique is employed to handle the uncertainty of hydrogen demand. The presented model is verified through a case study in Fujian Province, China.